2023
DOI: 10.3389/fpubh.2023.1130099
|View full text |Cite
|
Sign up to set email alerts
|

How both positive and burdensome caregiver experiences are associated with care recipient cognitive performance: Evidence from the National Health and Aging Trends Study and National Study of Caregiving

Abstract: IntroductionBeing an informal caregiver to a person with chronic disease, including persons living with dementia (PLWD), is a big role to take on and many caregivers experience both substantial burden and emotional reward related to caregiving. Care recipient factors (e.g., behavioral symptoms) are associated with caregiver experience. However, the relationship between caregiver and care recipient is bidirectional, so it is likely that caregiver factors impact the care recipient, though few studies have invest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 35 publications
(42 reference statements)
0
3
0
Order By: Relevance
“…This finding is consistent with our previous cross-sectional study [ 33 ]. Existing literature has consistently reported that many factors, such as caregivers’ race, age and care recipients’ cognitive functions impact the dementia caregiving experience [ 64 , 65 ]. Considering the notable differences in race, age and education level between spousal and adult–child caregivers, along with the variations in dementia status of care recipients in these two groups, our findings show that the impact of relationship type on caregivers’ QoL trajectories can be influenced by caregivers’ socio-demographics and care recipients’ dementia status.…”
Section: Discussionmentioning
confidence: 99%
“…This finding is consistent with our previous cross-sectional study [ 33 ]. Existing literature has consistently reported that many factors, such as caregivers’ race, age and care recipients’ cognitive functions impact the dementia caregiving experience [ 64 , 65 ]. Considering the notable differences in race, age and education level between spousal and adult–child caregivers, along with the variations in dementia status of care recipients in these two groups, our findings show that the impact of relationship type on caregivers’ QoL trajectories can be influenced by caregivers’ socio-demographics and care recipients’ dementia status.…”
Section: Discussionmentioning
confidence: 99%
“…445 In the 2011 National Study of Caregiving, greater satisfaction from dementia caregiving was associated with more emotional support from family members and friends. 514 Although caregivers report positive feelings about caregiving, such as family togetherness and the satisfaction of helping others, A10 , 515 , 516 , 517 , 518 , 519 , 520 , 521 , 522 , 523 they also frequently report higher levels of burden and stress; depression or other adverse mental health outcomes; strain; and problems with navigating care transitions when compared with other caregivers or non‐caregivers.…”
Section: Caregivingmentioning
confidence: 99%
“…Caregivers often do not have the necessary preparation to take care of patients during the acute phase of COVID‐19, and care poses a serious challenge for them (Ebrahimi et al, 2022 ). However, the burden of caregiving also encompasses positive aspects, such as imbuing caregivers' lives with a sense of meaning, experiencing the joy of being able to provide care and enhancing their personal satisfaction (Hilgeman et al, 2007 ; Wennberg et al, 2023 ). Research indicates that caregivers in Iran who tend to COVID‐19 patients experience significant caregiving burdens due to various factors (Jouybari et al, 2022 ; Mirzaei et al, 2020 ; Shafiezadeh et al, 2019 ; Sheikhbardsiri et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…serious challenge for them (Ebrahimi et al, 2022). However, the burden of caregiving also encompasses positive aspects, such as imbuing caregivers' lives with a sense of meaning, experiencing the joy of being able to provide care and enhancing their personal satisfaction (Hilgeman et al, 2007;Wennberg et al, 2023).…”
mentioning
confidence: 99%